Saxagliptin for the treatment of type 2 diabetes mellitus: assessing cardiovascular data - Cobble, Michael E (BioMed Central, 2012)
Patients with type 2 diabetes mellitus (T2DM) are at high risk for cardiovascular (CV) disease; however, conclusive evidence that glycemic control leads to improved cardiovascular outcomes is lacking. Saxagliptin is a potent, selective dipeptidyl peptidase-4 inhibitor approved as an adjunct to diet and exercise to improve glycemic control in adults with T2DM. Saxagliptin was evaluated in a series of phase III trials as monotherapy; add-on therapy to metformin, a sulfonylurea, or a thiazolidinedione; and as initial therapy in combination with metformin. Saxagliptin consistently improved glycemic control (as reflected by significant decreases in glycated hemoglobin, fasting plasma glucose, and postprandial glucose compared with controls) and was generally well tolerated. In these analyses, saxagliptin had clinically neutral effects on body weight, blood pressure, lipid levels, and other markers of CV risk compared with controls. A retrospective meta-analysis of 8 phase II and phase III trials found no evidence that saxagliptin increases CV risk in patients with T2DM (Cox proportional hazard ratio, 0.43; 95% CI, 0.23-0.80 for major adverse cardiovascular events retrospectively adjudicated). Instead, it raised the hypothesis that saxagliptin may reduce the risk of major adverse CV events. A long-term CV outcome trial, Saxagliptin Assessment of Vascular Outcomes Recorded in Patients with Diabetes Mellitus-THrombolysis in Myocardial Infarction 53 (SAVOR-TIMI 53) is currently ongoing to determine whether saxagliptin reduces CV risk in T2DM.